2018
DOI: 10.1002/anie.201802015
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis and Biological Investigation of (−)‐Artemisinin: The Antimalarial Activity of Artemisinin Is not Stereospecific

Abstract: Here, we describe an efficient and diversity-oriented entry to both (-)-artemisinin (1) and its natural antipode (+)-artemisinin, starting from commercially and readily available S-(+)- and R-(-)-citronellene, respectively. Subsequently, we answered the still open question regarding the specificity of artemisinins action. By using a drug-sensitive Plasmodium falciparum NF54 strain, we showed that the antimalarial activity of artemisinin is not stereospecific. Our straightforward and biomimetic approach to this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…Our synthesis (Scheme 1) started from the known and readily available aldehyde 3 [14] which was treated with the organolithium species obtained from derivative 4 [15] and n -BuLi to yield derivative 5 . The latter afforded allylic alcohol 6 after reduction of the propargylic moiety with Red-Al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our synthesis (Scheme 1) started from the known and readily available aldehyde 3 [14] which was treated with the organolithium species obtained from derivative 4 [15] and n -BuLi to yield derivative 5 . The latter afforded allylic alcohol 6 after reduction of the propargylic moiety with Red-Al.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we evaluated the antimalarial activity of (+)-3-hydroxymethylartemisinin ( 2 ) as well as of the derivatives 16 and 18 against the drug-sensitive P. falciparum NF54 strain as described previously [14]. We found them to be inactive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On a different note, Krieger et al synthesized synthetic enantiomer, (−)-artemisinin, and showed that the antimalarial activity of artemisinin is not stereospecific (Table 1 ) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The enantiomer 9 of the natural antimalarial sesquiterpenoid artemisinin has been synthesised and shown to have the same antimalarial activity as the natural isomer. 8 Four antibacterial sesquiterpene-α-amino acid hybrids, such as stereumamide A 10, have been isolated from the mushroom Stereum hirsutum. 9 The stereumamides are the first examples of sesquiterpenoid-α-amino acid quaternary ammonium salts from natural sources.…”
mentioning
confidence: 99%